Gender and Entrepreneurship in Pandemic Time: What Demands and What Resources? An Exploratory Study - De Simone, Silvia; Pileri, Jessica; Rapp-Ricciardi, Max; Barbieri, Barbara (Frontiers in Psychology, 2021)
Due to the COVID-19 epidemic, global economies have suffered an exogenous shock never seen be-fore with a strong economic and psychosocial impact on organization field. Italy, the context of our research, has been severely affected. The economic crisis has mainly affected women. In this scenario, entrepreneurial perceived success (objective and subjective) is influenced by increasingly burdensome job demands that entrepreneurs have to face up. Using the Job Demand-Resources model, the study aims to broaden the knowledge of the determinants of entrepreneurial perceived success in the current emergency moment. In particular, as regards of the demands, alongside the specific entrepreneurial demands (Time Demands, Uncertainty & Risk, Responsibility) we also decided to include the negative interface family-work in both directions from-family-to-work (NEGWIF) and from-work-to-family (NEGFIW). Regarding the resources, we considered entrepreneurial self-efficacy (Researching, Planning, Marshalling, Implementing People, Implementing Financial), Proactive and Elaborate social strategies, and both directions of the positive interface: from-family-to-work (POSWIF) and from-work-to-family (POSFIW). All participants are women entrepreneurs (N=137) who have completed a self-report questionnaire. We explored the associations between demands, resources, and the dimensions of success through hierarchical regressions. As for the Demands, Time Demands, Uncertainty & Risk, NEGWIF and NEGFIW negatively influenced perceived entrepreneurial success. Regarding resources, Planning, Implementing Financial, Proactive and Elaborate Social Strategies positively influenced the perceived entrepreneurial success.